Pregnancy Loss and Carotid Intima–Media Thickness in Mexican Women. Issue 2 (13th January 2018) - Hartasanchez, Sandra A.; Flores‐Torres, Mario; Monge, Adriana; Yunes, Elsa; Rodriguez, Beatriz; Cantu‐Brito, Carlos; Colaci, Daniela; Lamadrid‐Figueroa, Hector; Lopez‐Ridaura, Ruy; Lajous, Martin
Abstract : Background: Cardiovascular disease in women often develops without conventional risk factors. Prenatal loss is a common pregnancy outcome that may result in physiological changes can increase the potential future risk of cardiovascular disease. Insufficient information exists regarding the impact of pregnancy loss on early markers of cardiovascular disease risk. Methods and Results: Cross‐sectional analysis of 1767 disease‐free women from the MTC (Mexican Teachers' Cohort) who had been pregnant was used to evaluate the relationship between pregnancy loss and carotid intima–media thickness (IMT). Participants responded to a questionnaire regarding their reproductive history, risk factors, and medical conditions. We defined pregnancy loss as history of miscarriage and/or stillbirth. Trained neurologists measured IMT using ultrasound. We log‐transformed IMT and defined subclinical carotid atherosclerosis (SCA) as IMT ≥0.8 mm and/or plaque. We used multivariable linear and logistic regression models to assess the relation of pregnancy loss, IMT, and SCA. The mean age of participants was 49.8±5.1 years. The prevalence of pregnancy loss was 22%, and we observed SCA in 23% of participants. Comparing participants who reported a pregnancy loss and those who did not, the multivariable‐adjusted odds ratio for SCA was 1.52 (95% confidence interval, 1.12–2.06). Women who experienced a stillbirth had 2.32 higher odds (95% confidence interval, 1.03–5.21) of SCA than those who did not. Mean IMT appeared to be higher in women who reported a pregnancy loss relative to those who did not; nevertheless, this was not statistically significant. Conclusions: Pregnancy loss could be linked to cardiovascular disease later in life. The key findings of our study await confirmation and further investigation of the potential underlying mechanisms for this association is required.